EFEKTIVITAS MODUL BIMBINGAN KELOMPOK TEKNIK OUTBOND UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA - Setiawan, Antonius Ian Bayu (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
One of the crisis behaviors experienced by middle school students is low self-confidence. Low self-confidence will cause students to have difficulty finding success in life because self-confidence is one part of self-esteem. Therefore, strategic steps are needed to help resolve these problems, one of which is providing outbound technical group guidance interventions. The aim of this study was to determine the effectiveness of the outbound technique group guidance module as an effort to increase student self-confidence. The research uses a quantitative approach with a one-group pretest-posttest design type of experiment. The subjects of this research were 96 students of MAN 1 Kulonprogo who were selected based on a simple random sampling technique. The research will measure students' level of self-confidence using a self-confidence scale instrument, which will then be tested statistically using the T test. The results of the research show positive changes in self-confidence scores in the pretest (M = 118.4) and posttest (M = 137.80). The difference in scores shows a significant increase in scores, as evidenced by the results of the T test, namely a significance value of 0.000 < 0.05, meaning that the intervention carried out was proven to be effective in increasing students' self-confidence. The use of outbound technical group guidance has been empirically proven to increase students' self-confidence. Through outbound activities, students experience cognitive, affective, and psychomotor learning processes so that they can more easily develop aspects of self-confidence such as personal abilities, social interactions, and self-concept.